Comparison of temporal-spatial gait parameter in patients with osteoarthritis knee: an observational cross-sectional study - Rastogi, Aavrati; Kalia, Roop B.; Singh, Vivek (International Journal of Research in Medical Sciences, 2024)
Background: Osteoarthritis knee (OA) symptoms, including pain, joint stiffness, reduced joint movement, and muscle strength, can affect gait kinetics, kinematics, and temporal-spatial characteristics. Spatial-temporal gait parameters are useful for assessing and identifying clinically significant changes in an individual’s gait patterns and helps in rehabilitation. Methods: In this study 108 patients diagnosed with osteoarthritis knee according to EULAR classification knee OA were included in study. Age, gender and BMI were recorded for pain and function WOMAC Score was used, gait analysis was done to evaluate difference in temporo-spatial gait parameters between OA knee patients with KL grade 2 and 3. Results: A total of 108 patients with osteoarthritis knee were enrolled, including 40 men and 68 women. Total mean age was 55.92±9.05 years with P-value <0.05, and their average BMI was 27.24 kg/m2. Total WOMAC score mean 29.3±1.03. Mean WOMAC scores for pain 4.57±3.26, stiffness 2.60±0.12, function score 22.20±7.55 respectively. There was no significance difference between KL grade II and III including gender in temporal spatial gait parameters. Conclusions: This study suggests there is no significant difference in temporal-spatial gait parameters between Kl grade 2 and 3. Potential confounders including age, gender, BMI disease severity did not alter magnitude, although 95% CI.